Penerapan Social Media Marketing Pada Kinasih Resort & Conference Bogor - Muchtar, Sephia Herliana; Sulistiono, Sulistiono; Mulyana, Ade (Program Vokasi dan LPPM IBI Kesatuan, 2024)
Marketers today view social media as a great potential to increase market share. Companies can use social media marketing to sell products, build brand equity, and grow greater customer loyalty. This study aims to determine: 1) Implementation of social media marketing at Kinasih Resort & Conference Bogor; 2) Obstacles in implementing social media marketing at Kinasih Resort & Conference Bogor; 3) How to overcome obstacles in implementing social media marketing at Kinasih Resort & Conference Bogor. The results of this study include: 1) Implementation of social media marketing including utilizing social media platform features, creating account identities, and communicating with prospects through broadcasts; 2) Obstacles that arise in implementing social media marketing including obstacles in increasing traffic and leads because targets often respond slowly to communication; 3) solutions that have been implemented by the company include diligently checking targets and rechecking in making offers. Keywords: social media marketing, digital marketing, social media